2022
DOI: 10.1038/s41598-022-15988-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional dentoalveolar changes in open bite treatment in mixed dentition, spurs/posterior build-ups versus spurs alone: 1-year follow-up randomized clinical trial

Abstract: This randomized clinical trial aimed to compare the three-dimensional dentoalveolar maxillary changes after anterior open bite treatment with bonded spurs and build-ups versus bonded spurs alone. Patients from 7 to 11 years of age with anterior open bite were randomly allocated into two groups. Bonded spurs and posterior build-ups were used in the experimental group and only bonded spurs were used in the comparison group. The randomization sequence was generated at www.randomization.com. Opaque, sealed and seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
(110 reference statements)
0
7
0
1
Order By: Relevance
“…A specific bias assessment strategy was employed to evaluate the methodological quality and risk of bias in the selected clinical studies. Two different tools were used for this purpose: the RoB-2 (Risk of Bias 2) tool for RCTs [ 9 ] and the Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tool [ 10 ], as shown in Figures 1 - 2 [ 11 - 21 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A specific bias assessment strategy was employed to evaluate the methodological quality and risk of bias in the selected clinical studies. Two different tools were used for this purpose: the RoB-2 (Risk of Bias 2) tool for RCTs [ 9 ] and the Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tool [ 10 ], as shown in Figures 1 - 2 [ 11 - 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…The results of an RCT [ 11 ] comparing bonded spurs alone and with build-ups showed that both treatment procedures had moderate success rates for anterior OBR correction, with rates of 67% and 72% after a 12-month follow-up. Another retrospective study [ 12 ] focused on mandibular orthognathic surgery and found satisfactory occlusal stability at the one-year postoperative assessment in groups with little to no OBR.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations